Resistance to Cry Intensive Sleep Intervention in Young Children: Are We Ignoring Children’s Cries or Parental Concerns? - Sarah, B.; Hayley, E.; Hauck, Yvonne (2016)
The majority of behavioural sleep interventions for young children (defined as 5 years of age or less) involve extinction procedures where parents must ignore their child’s cries for a period. Many parents have difficulties implementing and maintaining these procedures, leading to attrition, non-compliance and treatment avoidance. Yet the reasons for these methods being difficult to implement for parents have not been well understood or addressed in the literature. In fact, they are being ignored. We discuss that understanding and addressing parental concerns may enable better targeted sleep interventions.